Effects Of Doping Concentration And Annealing Temperature On Indium Doped Zinc Oxide Particles Prepared Via Sol-Gel Method - Abd Manaf, Mohd Edeerozey; Abdullah Sani, Nurhernida; Ahsan, Qumrul; Wan Omar, Wan Mohamad Syarifudin; Mohamad Yatim, Norazlina; Yaakob, Mohd Yuhazri (Microscopy Society of Malaysia, 2020)
Doping of indium in zinc oxide (ZnO) is one of the means to increase its electrical conductivity. This study focuses on investigating the effects of indium doping concentration (In/Zn = 3%, 5% and 7%) and annealing temperature (200°C, 300°C and 450°C) on the electrical conductivity, structural, morphological and elemental properties of the indium doped zinc oxide (IZO) particles. The synthesis of IZO particles was carried out by a simple sol-gel method where sol-gel was evaporated to xerogel, heat treated and milled to form solid particles. The particles were characterized by four-point probe, X-ray diffraction (XRD), Fourier transform infrared (FTIR) and scanning electron microscopy-energy dispersive X-ray spectroscopy (SEM-EDX). The results obtained demonstrate an impressive increase of electrical conductivity by one order of magnitude at 5% of indium doping compared to the pristine zinc oxide (ZnO) as a result of cumulative charge carriers. Besides, an increase of annealing temperature also shows a positive effect on the electrical conductivity. XRD results show distinctive changes on crystal structure of polycrystalline wurtzite structure and its crystallite size with the change in parameters. FTIR results indicate the effects of both parameters by the presence and elimination of peaks designated for IZO functional group. The SEM-EDX analysis reveals the microstructure morphology at different parameters and validates the existence of each element according to doping concentration